Carolingian Pfalzen and law - Wamers, Egon (Danish Journal of Archaeology, 2017)
The palaces (Pfalzen) of the Carolingian period, which had developed from the Frankish royal manors, were a completely new form of building in the eastern Empire. Their architecture reflected central functions of the new kingship. In spite of all the variations in those palaces that have been the subject of archaeological research (for example Aachen, Paderborn, Ingelheim, Frankfurt), a constant triad of worldly representation, religious cult practice and economical power is always discernible. This article considers the question of the juridical character of the palaces: the extent to which they were the expression of the structures of power and law within the Carolingian Empire, in other words served a function within the court offices and the manorial system: the extent to which they functioned as the seats of law-making and judgement; and the extent to which their architectural iconography and physical symbolism reflects acts and forms of a juridical practice that had its roots in the roman law. (Translation: David Wigg-Wolf).